Analisis Rasio Keuangan PT Sentra Food Indonesia Tbk. Pada Bursa Efek Indonesia - Sulaiaman; Monoarfa, Sulerski (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2023)
The title of scientific research is Analysis of the financial ratios of PT Sentra Food Indonesia Tbk. on the Indonesia Stock Exchange. The purpose of the study was to analyze both the liquidity, solvency, activity and profitability ratios of PT Sentra Food Indonesia Tbk. on the Indonesia Stock Exchange. The data analysis method used in this research is quantitative analysis method in the form or approach of financial ratios are current ratio, quick ratio, debt to total asset ratio, debt to equity ratio, total assets turnover, receivable turnover, inventory turnover, economic profitability and own capital profitability. Based on the results of the analysis of the financial ratios of PT Sentra Food Indonesia Tbk. on the Indonesia Stock Exchange, the discussion is that the liquidity ratio in terms of current ratio and quick ratio of PT Sentra Food Indonesia Tbk. over the past five years (217 - 2021) fluctuated in nature, the solvency ratio in terms of total debt ti total asset ratio and total debt to equity ratio of PT Sentra Food Indonesia Tbk. over the past five years (217 - 2021) the average ratio for each period was 279.02%. fluctuating in nature. The activity ratio in terms of total asset turnover, receivable turnover and inventory turnover of PT Sentra Food Indonesia Tbk. over the past five years (217 - 2021) tends to decrease. The profitability ratio in terms of economic profitability and equity ratio of PT Sentra Food Indonesia Tbk. over the past five years (217 - 2021) tends to decrease.